FW propagation and absorption in reactor plasmas in the ICR frequency range at the quasiperpendicular propagation - Pavlov, S.S. (Вопросы атомной науки и техники, 2015)
On the base of the numerical model, taking into account the strong transverse and longitudinal dispersion of plasma, the absorption and dispersion of the Fast Mode of fast magnetosonic wave (FW) near ICR harmonics ω=nωci at the quasiperpendicular propagation regime were investigated. It was shown that in the region of small longitudinal refractive index values NII there appears the additional absorption that provides the value of optical thickness τ being constant in the entire region of additional absorption. At first and second harmonics the additional absorption can be interesting for FW plasma heating in the reactor-size devices. For higher harmonics it can be important for HF diagnostic purposes and for investigation of astrophysical plasmas. Дисперсия и поглощение быстрой моды быстрой магнитозвуковой волны (БВ) в области ионных циклотронных гармоник ω=nωci исследованы на основе численной модели, учитывающей сильную продольную и поперечную дисперсии плазмы. Показано, что в области малых продольных замедлений появляется дополнительное поглощение, которое обеспечивает постоянное значение оптической толщи во всей области проявления дополнительного поглощения. На первой и второй гармониках такое поглощение может быть интересно для нагрева реакторной плазмы. Для более высоких гармоник оно может быть важным для ВЧ-диагностики, а также для исследования астрофизической плазмы. Дисперсія і поглинання швидкої моди швидкої магнітозвукової хвилі (ШХ) в області іонних циклотронних гармонік ω=nωci досліджені на основі чисельної моделі, що враховує сильну поздовжню і поперечну дисперсії плазми. Показано, що в області малих поздовжніх уповільнень з'являється додаткове поглинання, яке забезпечує постійне значення оптичної товщі у всій області прояви додаткового поглинання. На першій і другій гармоніках таке поглинання може бути цікавим для нагріву реакторної плазми. Для більш високих гармонік воно може бути важливим для ВЧ-діагностики, а також для дослідження астрофізичної плазми.